Peripheral versus central cannulation of VA-ECMO for primary graft dysfunction after heart transplantation: A systematic review and meta-analysis - Eduard Ródenas-Alesina, MD; Aleix Olivella, MD; Ani Orchanian-Cheff, MiST; Farid Foroutan, PhD; Yasbanoo Moayedi, MD, MSc; Vivek Rao, MD, PhD; Filio Billia, MD, PhD; Heather J. Ross, MD, MHSc; Ana Carolina Alba, MD, PhD; Natasha Aleksova, MD, MSc (JHLT Open)
Background: Severe primary graft dysfunction (PGD) after heart transplantation (HT) is a major cause of death and requires veno-arterial extracorporeal membrane oxygenation (VA-ECMO). Methods: We conducted a systematic review and meta-analysis including studies of adult HT recipients who required VA-ECMO for PGD to determine whether a peripheral or central configuration was associated with higher mortality. The primary endpoints were short-term and one-year mortality. Secondary endpoints were VA-ECMO-related complications. Results: Overall, we included 16 studies comprising 874 patients from 33 centers. Using a random-effects model, peripheral cannulation was associated with a nonsignificant reduction in short-term mortality (odds ratios [OR] = 0.73, 95% confidence interval [CI] = 0.41-1.28, I2 = 55.8%) and a significant reduction in 1-year mortality (OR = 0.60, 95%CI = 0.37-0.97, I2 = 35.9%). Peripheral cannulation decreased the risk of bleeding but increased the risk of limb ischemia and infection, with similar rates of stroke and need for renal replacement therapy. Overall, certainty of evidence was low. Conclusions: With low certainty evidence, peripheral VA-ECMO cannulation may reduce short-term and 1-year mortality with lower bleeding rates but higher limb-related complications, supporting peripheral configuration in HT recipients with severe PGD.